Mitochondria-dependent benzothiadiazole-based molecule probe for quantitatively intracellular pH imaging. (October 2017) - Han, Xiao; Wang, Zhiru; Cheng, Qing; Meng, Xiangru; Wei, Donghui; Zheng, Yichao; Ding, Jie; Hou, Hongwei
Abstract: In this work, we reported two new pH-sensitive benzothiadiazole- pyridine compounds1 and2, which distinctly showed the red-shifted absorption and "turn-off" fluorescence responses to increased pH in a broad range (pH = 2–12). Because of excllent mitochondria-immobilized preformance, suitable fluorescence detection window and linear response behavior in the range of pH = 5–8, compound1 was suitable to explore as a imaging detector of intracelluar pH in live cell. More intereastingly, different from "turn-off" fluorescence response to increased pH in buffer solution, probe1 displayed a "turn-on" fluorescence in live cell imaging experiment. This opposite performance between buffer solution and live cell are so unique that no such literature has been ever mentioned in our best knowledge. The further study revealed that this unique performance was dependent on the mitochondrial function under different physiological pH conditions. Herein, on the basis of special "turn-on" fluorescence response, intracellular pH was successfully imaged in a quantitatively ratiometric method by using1 in conjunction with MitoTracker Red (MTR). Graphical abstract: In this paper, we reported the first example for quantitatively intracellular pH probe dependent on mitochondrial function under different physiological pH conditions. Highlights: Two new benzothiadiazole-pyridine compounds were pH-sensitive in broad ranges (2–12). In live cell imaging experiment, unique "turn-on" fluorescence response to increased pH was firstly observed. The unique performance was dependent on mitochondrial function under different physiological pH conditions. The first mitochondria-dependent benzothiadiazole- pyridine probe for cellular pH imaging in quantitative mode.